Comparison between different methods for the assessment of the VO2 slow component of freestyle elite swimmers - Querido, A.; Machado, L.; Keskinen, K. L.; Vilar, S.; Cardoso, C.; Cruz, A.; Vilas-Boas, J. P.; Fernandeas, R. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study is to compare different methods for the assessment of the Oxygen uptake Slow Component (SC) in elite swimmers in a time limit test at the minimum velocity that elicits maximal oxygen consumption. Five females and two males participated in this study. VO2 was measured by a portable gas analyser connected to the swimmers by a respiratory snorkel. To describe the SC kinetics was used a mathematical model with three exponential functions. This model was compared with different methods of rigid time intervals defined as the difference between the final VO2 and that at the 2nd min (deltaVO2[end-2] or at the 3rd min of exercise (deltaVO2[end-3]). This study showed that the use of the VO2[end-3] underestimates the results since the SC usually begins earlier than the 3rd minute and that the use of the VO2[end-2] seems to be a good solution, being less accurate but more simple to use in a day-to-day basis.